Edukasi Pencegahan Dan Penanggulangan Anemia Pada Remaja Putri - Yusnita; Lisma Luciana; Muhammad Shalahuddin; Isni, Isni Hijriana (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Anemia or lack of iron is a problem for young women that must be addressed. Anemia can cause the body to tire easily, decrease productivity and creativity, weaken the immune system so that it is easily attacked by disease. Young women are a group that is vulnerable to anemia. Anemia in young women will have a long-term impact if not treated properly. Efforts to prevent anemia need to be carried out actively and continuously. One effort that can be made is education about blood-boosting tablets and nutrition that can prevent anemia. The goal after this Health counseling is expected to increase the knowledge of young women in preventing and overcoming anemia. The method used in this community service activity is the lecture and discussion method through several stages, namely the preparation, implementation and evaluation stages. The results of this activity are an increase in knowledge in young women about the prevention and overcoming of anemia by increasing nutrition, consuming food sources of iron and iron supplementation.